2018
DOI: 10.1158/1940-6207.capr-17-0245
|View full text |Cite
|
Sign up to set email alerts
|

Macrophagic “Crown-like Structures” Are Associated with an Increased Risk of Breast Cancer in Benign Breast Disease

Abstract: In breast adipose tissue, macrophages that encircle damaged adipocytes form "crown-like structures of breast" (CLS-B). Although CLS-B have been associated with breast cancer, their role in benign breast disease (BBD) and early carcinogenesis is not understood. We evaluated breast biopsies from three age-matched groups ( = 86 each, mean age 55 years), including normal tissue donors of the Susan G. Komen for the Cure Tissue Bank (KTB), and subjects in the Mayo Clinic Benign Breast Disease Cohort who developed ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 33 publications
2
55
0
Order By: Relevance
“…Consistent with these observations, Carter et al recently reported that high levels of breast white adipose inflammation were associated with increased breast cancer risk. 36 …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these observations, Carter et al recently reported that high levels of breast white adipose inflammation were associated with increased breast cancer risk. 36 …”
Section: Discussionmentioning
confidence: 99%
“…In engineered mice, reduced levels of SIRT1 in adipose tissue have been associated with macrophage influx and the development of adipose inflammation (34,35). A similar low-grade inflammatory process was recently linked to the pathogenesis of human breast cancer (36,37). Taken together, the observed reduction in SIRT1 in the breast tissue of obese women may be causally linked to both subclinical inflammation and elevated aromatase expression, contributing to the increased risk of hormone receptor-positive breast cancer in obese postmenopausal women.…”
Section: Figure 8 Atf3 Is Important For Pge 2 -Mediated Down-regulatmentioning
confidence: 94%
“…A distinct feature of low-grade inflammation in AT is the formation of crown-like structures (CLS) which are syncytial arrangements comprised of encircled necrotic/damaged adipocytes with macrophages. The presence of CLS is associated with elevated levels of inflammatory mediators, mainly TNFα and prostaglandin E2 [53]. Investigations have revealed that these macrophages may resorb the lipid remnants of encircled dead adipocytes and also contribute to inflammation [54].…”
Section: Role Of Monocytes and Macrophage Within Atmentioning
confidence: 99%